The Puzzle of Brazil's High Interest Rates - Segura-Ubiergo, Alex (IMF Working Papers; Working Paper, 2012)
This paper highlights that real interest rates in Brazil have declined substantially over time, but are still well above the average of emerging market inflation targeting regimes. The adoption of an inflation-targeting regime and better economic fundamentals (reduction in inflation volatility and improvements in the fiscal and external positions) has helped Brazil sustain significantly lower real interest rates than in the past. Going forward, the paper shows that Brazil can converge towards lower equilibrium real interest rates if domestic savings increase to the level of other emerging market countries. The effect is particularly pronounced if the increase in domestic savings is achieved through higher levels of public savings. Still, econometric results suggest that, controlling for everything else in the model, real interest rates in Brazil are about two full percentage points higher than in other countries in the sample, suggesting that there are still Brazil-specific factors that have not been captured by the empirical analysis. Some of these factors may include credit market segmentation and inflation inertia generated by still pervasive indexation practices.